Gêneros brasileiros a quatro mãos para o iniciante de piano: um estudo de aspectos motivacionais, técnicos e estilísticos em oito peças de Ricardo Nakamura - Deborah Fernandes Nilson (2005)
This study investigates the applicability of an unreleased repertoire for four-hand piano composed according to four Brazilian music genres: choro, samba, baião and bossa nova. This applicability was observed based on the motivation, the validity of the four hands practice and the teaching and learning processes. This research had been guided by the C(L)A(S)P model and has contemplated the modalities of musical behaviour proposed by Swanwick (1979), except for composition, which was not the focus of the study. Results confirm the didactic, esthetic and stylistic value of the material, as well as the validity of teaching by imitation and by ear, the advantages of playing four hands, the accessibility of the pieces, the value of Brazilian musical styles, the importance of stylistic appreciation and knowledge and the role of motivation in the learning process. We aim at collaborating not only for the refinement of this specific repertoire, but also for expanding the musical universe of both students and teachers. Besides, from the finding that there is a lack musically rich and interesting materials that can approximate children to Brazilian music, we hope that this study may encourage professionals, composers and educators in creation and selection a repertoire of this nature for early instrumental teaching.